1991
DOI: 10.1007/bf01025251
|View full text |Cite
|
Sign up to set email alerts
|

Heptad motifs within the distal subdomain of the coiled-coil rod region of M protein from rheumatic fever and nephritis associated serotypes of group A streptococci are distinct from each other: Nucleotide sequence of the M57 gene and relation of the deduced amino acid sequence to other M proteins

Abstract: Streptococcal M protein, a dimeric alpha helical coiled-coil molecule, is an antigenically variable virulence factor on the surface of the bacteria. Our recent conformational analysis of the complete sequence of the M6 protein led us to propose a basic model for the M protein consisting of an extended central coiled-coil rod domain flanked by a variable N-terminal and a conserved C-terminal end domains. The central coiled-coil rod domain of M protein, which constitutes the major part of the M molecule, is made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 45 publications
2
20
0
1
Order By: Relevance
“…However, the response of PLN cells from rM5-immunized mice to sM5[300-3191 was not detectable, as shown previously, whereas sM5 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] induced significant responses, as achieved previously with the longer peptide M5[1-35] (28).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, the response of PLN cells from rM5-immunized mice to sM5[300-3191 was not detectable, as shown previously, whereas sM5 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] induced significant responses, as achieved previously with the longer peptide M5[1-35] (28).…”
Section: Resultssupporting
confidence: 61%
“…Groups of BALB/c mice were immunized with synthetic peptides in FCA and boosted with the same peptide in FIA to determine whether T-cell recognition sites within the peptide could provide help for anti-peptide antibody responses. IgG was measured by ELISA in sera from individual mice immunized with sM5[300-319], sM5 [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], or rM5 ( Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…This association does not seem to be due to a metabolic relationship between enzymes involved in the biotypic delineation and the protein M epitopes. Indeed, it has been demonstrated that the antigenic diversity of protein M is associated with sequence and structure variations of polypeptidic variable regions (5,16). Restricted associations between unrelated phenotypic characteristics within the same species might be explained by different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The exceedingly high predicted a-helical values for the cellular antigens (X = 58 卤 4%) has been noted previously for several of these proteins and has been confirmed by direct structural analysis in a few cases. [19][20][21] The wide fluctuations in DNA base composition among bacteria and between different segments of the eukaryotic genome have most often been attributed to a directional mutation bias that pushes the G and C level of the entire genome or subgenomic segment toward some level.2,3'7,10 By analogy, we suggested that the asymmetrical variation in base frequencies of retroviral genomes arises from directional mutation biases imposed on the genomes when they reside in single-stranded states.13 One line of supporting evidence for this view was the observation that untranslated DNA and silent sites in coding sequences displayed biases that were similar to those that characterized the entire genomes. As shown in Table 2, influenza and tymoviruses display the characteristic biases in the third codon positions of the 4-fold degenerate codons.…”
Section: Resultsmentioning
confidence: 99%